Theory of diffusion to an "annular microband" electrode - Dickinson, E; Streeter, I; Compton, R (2009)
The finite difference method is used to perform 2D numerical simulation of chronoamperometry and voltammetry at a hypothesised "annular microband" (AMB) electrode. The diffusional properties of this electrode system are inferred from the results of simulations and are found to be highly efficient. Comparison is drawn with infinite limiting cases of the geometry, which are shown not to support mass-transport limited steady-state diffusion, whereas the AMB supports such a steady state. Lastly, the optimisation of the geometry is discussed in the context of the experimental application of voltammetry as a means to investigate rapid electrochemical kinetics. © 2008 Elsevier B.V. All rights reserved.